Implementation of digitization in dentistry from the year 2011 to 2021: A bibliometric analysis - Neelam Gavali; Alaka Chandak; Pramod Waghmare; Amol Jamkhande; Shams UL Nisa; Priyanka Shah (Wolters Kluwer Medknow Publications, 2023)
Introduction: Digitalization has revolutionized dentistry in the last decade. Current application in digitization has increased which includes use of various systems such as cone-beam computed tomography for implant purpose, temporomandibular joint disease diagnosis, utilization of computer-aided design-computer-aided manufacturing system (CAD-CAM system) for prosthodontics. The usage of digital dentistry is made right from diagnosis to treatment planning which reduces the time consumption & human efforts to a great extent & increases accuracy for treatment planning. Therefore, this review focuses on analysis of implementation of digitization in dentistry from 2011 to 2021. Objectives: This study aims to analyze the scientific literature on digitization in dentistry by examining the origin of manuscripts, study types, and levels of evidence. Materials and Methods: The study retrieved data from journals indexed in Scopus. Subsequently, a descriptive analysis was conducted on bibliographic data, collaboration network, and keyword co-occurrence. The articles were then classified based on their field of interest, main research question, study type, and level of evidence. Results: The study has identified 203 original papers on digital dentistry, published in 112 journals, and co-authored by 1436 individuals affiliated with 89 institutions from 45 countries. While the majority (81.4%) of these papers were from a single country, we observed high collaboration among institutions from the United States, Britain, and Brazil. The primary focus of these papers was on the potential uses of digital technology in dentistry. Regarding study type, most articles were systematic reviews, cross-sectional studies, and original research papers. Conclusion: Integrating digital technology in dentistry has brought numerous benefits, including a more organized and streamlined approach to medical records and thorough investigation and treatment planning within a shorter timeframe. Furthermore, digital technology enables the accurate detection of even the minutest details, minimizing errors and eliminating human bias. The use of three-dimensional imaging techniques allows for the precise determination of objects' geometrical characteristics and spatial orientation, resulting in the accurate placement of implants and prosthetics. Clinical Relevance: Digitization in dentistry has opened a whole new world for practitioners to focus on the patient satisfaction approach. Digital platforms can help optimize diagnosis and consulting and provide an excellent base for treatment planning.